Characterization of Cynara cardunculus L. flower from Alentejo as a coagulant agent for cheesemaking - Gomes, Sandra (2020)
This work was supported by the project ValBioTecCynara (ALT2003-0145- FEDER-000038) - Economic valorisation of Cardoon (Cynara cardunculus): study of natural variability and biotechnological applications), cofinanced by FEDER under the Alentejo 2020 Program.